A V2O5 nanorod decorated graphene/polypyrrole hybrid electrode: a potential candidate for supercapacitors. (25th January 2017) - De Adhikari, Amrita; Oraon, Ramesh; Tiwari, Santosh Kumar; Lee, Joong Hee; Kim, Nam Hoon; Nayak, Ganesh Chandra
Abstract : Electron hopping conduction of V2 O5 nanorod draped graphene/polypyrrole hybrid electrode materials for supercapacitor applications. Abstract : Vanadium pentoxide (V2 O5 ) nanorod decorated graphene polypyrrole nanocomposites have been synthesized successfully by a facile hydrothermal process for supercapacitor (SC) applications. The morphological study revealed the successful decoration of V2 O5 nanorods and polypyrrole (PPy) within the intergallery of graphitic materials due to their high degree of propensity for intercalation which leads to the formation of mesoporous 3D nanostructures. These mesoporous structures can efficiently allow fast diffusion and ion transport at the electrode–electrolyte interface towards high electrochemical utilization and superior performance. Here, decoration of V2 O5 within a polymer matrix along with a graphitic material renders different electrical profiles by virtue of their electron hopping within nanocomposites. Galvanostatic charging discharging revealed that VGP was found to be superior with a maximum specific capacitance of 787 F g −1 at a current density of 1 A g −1 using KCl as an electrolyte. These observations were also confirmed by electrochemical measurements through CV and EIS studies. Furthermore, cyclic stability performed for 5000 consecutive cycles also substantiate their high durability and high power delivery uptake. Thus, considering all such key features, V2 O5 based nanocomposites can be suitable for SC applications.